Assessments Regarding the Employed Population in Agriculture and The Added Value in The Agricultural Sector in Romania - Tudorel ANDREI (Communications of International Proceedings, 2021)
The paper aims to present some characteristics of the Romanian agriculture compared to the European Union countries. At European level, a small number of countries account for most of the gross value of agriculture. At the opposite, it is placed the agriculture in Romania. The employed population of this sector includes an important part of the employed population of the country, but in this sector the gross value added is still low. There are many causes of this situation.
Keywords: External Trade; Theil Index; Regression Model.